Improvement of rheological and physicochemical properties of longan honey by non-thermal magnetic technique - Vinyoo Sakdatorn (2018)
© 2018 Institute of Food Science and Technology. A non-thermal technology using magnetic field (MF) can improve flowability of honey while maintaining its physicochemical quality. Effects of MF treatment on rheological and physicochemical properties of longan honey exposed to MF for 2 h at 15 °C and 28 °C were investigated and compared with those of non-MF samples. Increasing MF strength at 28 °C caused a reduction in firmness (P ≤ 0.05), but not in consistency, index of viscosity and cohesiveness. The effects at 15 °C were greater. Newtonian behaviour was observed for all samples. Shear stress and viscosity were significantly reduced with increasing MF strength at 15 °C (P ≤ 0.05), but less at 28 °C. pH was also decreased. Total soluble solids content was increased at both temperatures (P ≤ 0.05). Colour index was not significantly affected by MF, whereas optical density was slightly increased at high MF strengths (P > 0.05). L* values for the MF treated samples were increased (P ≤ 0.05), giving lighter and more pleasant colour to the honey. MF treatment improved overall qualities of honey. International Journal of Food Science and Technology